Generative Artificial Intelligence in English Instruction: Indonesian EFL Vocational High School Teachers' Perspectives - Apoko, Tri Wintolo (Journal of Languages and Language Teaching, 2025)
Generative artificial intelligence (Gen-AI) tools havebeen widely used in English teaching and learning. However, in the context of EFL teachers in vocational high schools, not all the teachers are aware of the potential of Gen-AI for English instruction. This study aims to address the gap identified in previous research by investigating Indonesian EFL teachers' perceptions and challenges of integrating Gen-AI into their classrooms. The participants of this study were 37 EFL teachers from diverse vocational high schools in Eastern Jakarta, Indonesia. This study employed a sequential explanatory mixed-methods design, combining quantitative and qualitative data. A cross-sectional survey was conducted to identify the perceptions of teachers and the challenges they face when integrating Gen-AI in their teaching practices. A semi-structured interview was conducted with a subset of participants to gather qualitative data on their experiences and challenges in utilizing Gen-AI. The results of the survey reveal positive perceptionsamong EFL teachers regarding the use of Gen-AI in English classes (Mean=4.00, SD=0.53). The findings also reveal that teachers are confident and willing to adopt Gen-AI tools (Mean=3.92, SD=0.49) acknowledging their ease of use and practicality in daily teaching practices (Mean=3.92, SD=0.60) and aligning with industry-specific needs (Mean=3.95, SD=0.52).The study underscores the need for equitable access and professional development to support the effective use of Gen-AI in vocational EFL context, ultimately enabling more innovative and future-ready English instruction.